On the systematic placement of Pyreneplax Ossó, Domínguez & Artal, 2014 (Decapoda, Brachyura, Vultocinidae) - Ossó, Àlex; Domínguez, José Luis (Geologija, 2020)
Examination of the thoracic sternum and pleonal elements of a new male specimen of Pyreneplax basaensis Ossó, Domínguez & Artal, 2014 from the upper Eocene of northern Spain confirms its assignment to the family Vultocinidae Ng & Manuel-Santos, 2007 and reveals the presence of an old lineage (Pyreneplax and possible allies) that appeared during the Eocene, persisting to the present day.